Exploring the smart wearable payment device adoption intention: Using the symmetrical and asymmetrical analysis methods - Hayat, Naeem; Al Mamun, Abdullah; Salameh, Anas A.; Ali, Mohd Helmi; Hussain, Wan Mohd Hirwani Wan; Zainol, Noor Raihani (Frontiers in Psychology, 2022)
The smart wearable device is a new breed of mobile device that offers diversified utilities for health, sport, and finance for consumers worldwide. The current study aims to investigate the provocation of the intention to use smart wearable payment devices among Malaysian consumers. The unified theory of technology acceptance and use of technology (UTAUT) was employed with the cross-sectional survey-based data to explain the adoption of the smart wearable payment device. Furthermore, the UTAUT model was extended with trust and lifestyle compatibility factors to investigate smart wearable payment device adoption. The survey-based data was collected through the online survey and analysed through the symmetrical modelling approach of partial least squares structural education modelling (PLS-SEM) to evaluate theoretical associations between the study constructs. The fuzzy set qualitative comparative analysis (fsQCA) was employed as an asymmetrical approach. As a result, it was found that the ease of use, lifestyle compatibility, and trust significantly impacted the intention to adopt smart wearable payment devices. However, social influence and facilitating conditions did not support the intention of adopting smart wearable payment devices. Adopting these devices requires policy and infrastructure development to harness the adoption of smart wearable payment devices. This paper is concluded with study limitations and future research suggestions.